Blue-Water Empire : The British in the Mediterranean Since 1800 - Holland, R. F. (Robert F.) (London Penguin, 2013)
A narrative of Britain's military and cultural ties with the Mediterranean Sea. Evoking the conflicts and contrasts between British and local societies caught up in dramatic events, as well as their mutual resilience under pressure, it charts the British experience in the Mediterranean in the age of empire.
Include Index, Notes and Illustration
Keywords: Great Britain -- Mediterranean Region -- Civilization--Mediterranean influences